Fresno State Football Game Tailgate Sponsored by Fresno Rotary Club - Watkins, Howard::::::::: (1989)
Frances Kamp standing and Robin Watkins sitting at table with other Bulldog fans eating BBQ; Fresno Rotary banner in background